용존산소활량 측정용 지르코니아 갈바니 센서 - 오영제 (한국센서학회, 2009)
Magnesia partially stabilized zirconia(Mg-PSZ) solid electrolytes for an improvement of thermal shock resistance, which is suitable for the measurement of oxygen activity in a molten steel, were prepared by post-thermal aging treatment. The steelmaking oxygen sensor elements were formed by an injection molding method, sintered at 1650℃, and then thermal aged ranged from 1250 to 1400℃. Sintered density and porosity were decreased as increasing the magnesia content in a zirconia-magnesia solid solution. Fractions of cubic phase to the synthesized Mg-PSZ solid electrolytes were ranged from 13.13 to 79.54 % after post-thermal aging treatment. Very dense microstructure without voids in the grains was obtained by the post-thermal aging process. Fine tetragonal phase crystallites precipitated on the cubic surface during post- thermal aging up to 1300℃ improve a thermal shock resistance and reappearance of electro motive force(EMF) curve.